2013
DOI: 10.1130/g34415.1
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami recurrence revealed by Porites coral boulders in the southern Ryukyu Islands, Japan

Abstract: Information about past tsunami hazards, such as their recurrence interval and magnitude, is needed for future disaster prediction and mitigation. We examined radiocarbon ages of the surfaces of massive coral boulders cast ashore by past tsunamis in the southern Ryukyu Islands, Japan, where few historical and geological records of past tsunamis are available. We selected only non-eroded Porites coral boulders along the shoreline, because their characteristics make it possible to determine the probable timing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
73
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 19 publications
5
73
1
1
Order By: Relevance
“…The 14 C dates of other tsunami boulders from the southern Ryukyu Islands were examined by Kawana and Nakata (1994) and Goto et al (2010). Araoka et al (2013) recently estimated that large tsunamis have occurred at recurrence intervals of 150-400 years since at least 2400 years ago.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The 14 C dates of other tsunami boulders from the southern Ryukyu Islands were examined by Kawana and Nakata (1994) and Goto et al (2010). Araoka et al (2013) recently estimated that large tsunamis have occurred at recurrence intervals of 150-400 years since at least 2400 years ago.…”
Section: Study Areamentioning
confidence: 99%
“…Although previous paleotsunami research along the Ryukyu Trench has examined coralline boulders (herein, "tsunami boulders") (Kawana and Nakata 1994;Goto et al 2010;Araoka et al 2013), Ando et al (2018) recently identified three sandy tsunami deposits (T-I, T-II, and T-IV) and a layer of buried tsunami boulders (T-III) in a trench on Ishigaki Island (Figs. 1, 2, and 3).…”
Section: Introductionmentioning
confidence: 99%
“…The seriousness of these events underscores the need for further detailed investigations of the active geological structures in and around the source areas of these earthquakes and tsunamis, particularly at the plate convergent margins. The Ryukyu subduction zone is one such region that requires further study (Ando et al 2009) because of the numerous tsunami boulders that can be found widely scattered along the coasts of the southern Ryukyu Arc (e.g., Araoka et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This > 30 m high tsunami deposited numerous large coral boulders when it hit the Sakishima Islands (e.g., Nakata and Kawana 1995;Watanabe 1985). Such coral boulders have been known to provide useful geological paleo-tsunami records for estimating the recurrence intervals of large earthquakes along the Ryukyu Trench (e.g., Araoka et al 2013;Goto et al 2010). For example, Goto et al (2013) described the clast sizes of such coastal boulders, from which they identified the local occurrence of tsunamigenic earthquakes along the Ryukyu Arc.…”
Section: Introductionmentioning
confidence: 99%
“…Boulders of Holocene coral limestone that had been transported by tsunamis were distributed on the beach and land areas of the south Ryukyu Islands (Kawana and Nakata 1994;Goto et al 2010b). Based on dating of fossil coral on the boulders, the historical occurrences of several huge tsunamis were estimated on the south Ryukyu Islands (Kawana and Nakata 1994;Goto et al 2010b;Araoka et al 2013).…”
Section: Introductionmentioning
confidence: 99%